Community Empowerment and Circular Economy Implementation: Evidence from Waste Bank Programs - Aa Willy Nugraha; Yusuf Abdullah; Verra Rosyalia Widia; Mulia Amirullah (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
Waste management remains an environmental problem in many urban areas, including Ciakar Village, Cibeureum District, Tasikmalaya City. Low public awareness of waste segregation and proper waste management has led to an increasing volume of waste ending up in landfills. The circular economy approach through waste banks addresses environmental issues and generates economic value for the community. This community service program aims to empower local residents by optimizing waste bank operations in line with circular economy principles. The implementation methods include socialization activities, education, waste segregation training, and assistance in waste bank management. The results indicate improved community understanding of the circular economy concept, increased community participation in waste bank activities, and the establishment of a more structured community-based waste management system. This program contributes to reducing household waste generation while simultaneously enhancing the economic value potential of managed waste.